2001
DOI: 10.4049/jimmunol.166.9.5733
|View full text |Cite
|
Sign up to set email alerts
|

Improving Vaccine Potency Through Intercellular Spreading and Enhanced MHC Class I Presentation of Antigen

Abstract: The potency of naked DNA vaccines is limited by their inability to amplify and spread in vivo. VP22, a HSV-1 protein, has demonstrated the remarkable property of intercellular transport and may thus provide a unique approach for enhancing vaccine potency. Therefore, we created a novel fusion of VP22 with a model Ag, human papillomavirus type 16 E7, in a DNA vaccine that generated enhanced spreading and MHC class I presentation of Ag. These properties led to a dramatic increase in the number of E7-specific CD8+… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
91
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 131 publications
(94 citation statements)
references
References 30 publications
3
91
0
Order By: Relevance
“…The generation of pcDNA3-E7 has been described previously [5,25]. The generation of pcDNA3-CRT has also been described previously [5].…”
Section: Plasmid Dna Constructs and Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…The generation of pcDNA3-E7 has been described previously [5,25]. The generation of pcDNA3-CRT has also been described previously [5].…”
Section: Plasmid Dna Constructs and Preparationmentioning
confidence: 99%
“…Preparation of DNA-coated gold particles and gene gun particle-mediated DNA vaccinations were performed using a helium-driven gene gun according to a protocol described previously with some modifications [25]. Gene gun particle-mediated DNA vaccinations were performed using a Low Pressure-accelerated Gene Gun (BioWare Technologies Co. Ltd., Taipei, Taiwan).…”
Section: Dna Vaccinationmentioning
confidence: 99%
“…Such sequences, termed 'protein transduction domains' (PTDs), have been identified in the human immunodeficiency virus (HIV) tat protein, the herpes simplex virus (HSV) VP22 protein, the Drosophila melanogaster homeoproteins, and elsewhere (reviewed in Lindgren et al 9 and Prochiantz 10 ). These sequences have been successfully used as immunoadjuvants in several models, [11][12][13][14] and it has been postulated that the immune enhancement results from the improved delivery of these translocatory proteins to APCs. We have found that fusion of the HIV-1 tat PTD to an epitope enhanced its ability to stimulate CD8 þ T cells in vitro and in vivo, and improved antiviral protection when administered as a plasmid vaccine.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, the VP22 gene of BHV-1 has been used as a gene adjuvant to enhance the immunogenic activity and thus make the antigen easily recognized and processed by the organism immunity system, and VP22 can enhance immune responses in vivo in a variety of applications (Hung et al, 2001;Wills et al, 2001;Saha et al, 2006). In this work, VP22 was used as a gene adjuvant to study the enhancement of the SS DNA vaccine in mice.…”
Section: Discussionmentioning
confidence: 99%